A novel 3q29 deletion associated with autism, intellectual disability, psychiatric disorders, and obesity. Issue 2 (1st December 2015) - Biamino, Elisa; Di Gregorio, Eleonora; Belligni, Elga Fabia; Keller, Roberto; Riberi, Evelise; Gandione, Marina; Calcia, Alessandro; Mancini, Cecilia; Giorgio, Elisa; Cavalieri, Simona; Pappi, Patrizia; Talarico, Flavia; et al.
Abstract : Copy number variation (CNV) has been associated with a variety of neuropsychiatric disorders, including intellectual disability/developmental delay (ID/DD), autism spectrum disorder (ASD), and schizophrenia (SCZ). Often, individuals carrying the same pathogenic CNV display high clinical variability. By array‐CGH analysis, we identified a novel familial 3q29 deletion (1.36 Mb), centromeric to the 3q29 deletion region, which manifests with variable expressivity. The deletion was identified in a 3‐year‐old girl diagnosed with ID/DD and autism and segregated in six family members, all affected by severe psychiatric disorders including schizophrenia, major depression, anxiety disorder, and personality disorder. All individuals carrying the deletion were overweight or obese, and anomalies compatible with optic atrophy were observed in three out of four cases examined. Amongst the 10 genes encompassed by the deletion, the haploinsufficiency of Optic Atrophy 1 ( OPA1 ), associated with autosomal dominant optic atrophy, is likely responsible for the ophthalmological anomalies. We hypothesize that the haploinsufficiency of ATPase type 13A4 ( ATP13A4 ) and/or Hairy/Enhancer of Split Drosophila homolog 1 ( HES1 ) contribute to the neuropsychiatric phenotype, while HES1 deletion might underlie the overweight/obesity. In conclusion, we propose a novel contiguous gene syndrome due to a proximal 3q29 deletion variably associated with autism, ID/DD, psychiatric traits and overweight/obesity. © 2015 Wiley Periodicals, Inc.